Dare to Be Different? Conformity Versus Differentiation in Corporate Social Activities of Chinese Firms and Market Responses - Zhang, Yanlong; Wang, Heli; Zhou, Xiaoyu (Academy of Management Journal, 2020)
Building on the literature on optimal distinctiveness, this study explores the effects of conformity versus differentiation in corporate social responsibility (CSR) practices on evaluations by security analysts and responses of the financial market in general. We develop the argument that while conformity in CSR scope enhances analyst coverage, differentiation in CSR emphasis leads to more-favorable analyst recommendations and higher market value. This suggests that firms may be able to simultaneously conform in CSR scope and differentiate in CSR emphasis to achieve optimal distinctiveness. To further enhance our understanding of the variation in the relationship between conformity and differentiation and the response of analysts and the market, we investigate how some firm- and analyst-level factors moderate this relationship. Using the case of corporate social activities of Chinese listed firms during the period from 2008 to 2014, we show that scope conformity has a stronger effect on analyst coverage for state-owned firms and firms with higher visibility; on the other hand, the relationship between emphasis differentiation, and analyst recommendation and market value strengthens for firms covered by high-status brokerage houses but weakens for those experiencing high earnings pressure.